2021
DOI: 10.1101/2021.01.26.428331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Analysis of Protein Stability and Allosteric Interaction Networks in Distinct Conformational Forms of the SARS-CoV-2 Spike D614G Mutant: Reconciling Functional Mechanisms through Allosteric Model of Spike Regulation

Abstract: Structural and biochemical studies SARS-CoV-2 spike mutants with the enhanced infectivity have attracted significant attention and offered several mechanisms to explain the experimental data. The development of a unified view and a working model which is consistent with the diverse experimental data is an important focal point of the current work. In this study, we used an integrative computational approach to examine molecular mechanisms underlying functional effects of the D614G mutation by exploring atomist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 125 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…The D614G mutant prefers the one RBD “up” state 7 times more than the “three-down” configuration, while they are equally likely in the WT strain ( 54 ). The specific role of the D614G mutation was recently also established by coarse-grained MD study ( 72 ). Our model predicted the D614 residue as a key player in RBD dynamics from physics-based atomistic simulations without any prior knowledge of the mutation profile of the spike.…”
Section: Concluding Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The D614G mutant prefers the one RBD “up” state 7 times more than the “three-down” configuration, while they are equally likely in the WT strain ( 54 ). The specific role of the D614G mutation was recently also established by coarse-grained MD study ( 72 ). Our model predicted the D614 residue as a key player in RBD dynamics from physics-based atomistic simulations without any prior knowledge of the mutation profile of the spike.…”
Section: Concluding Discussionmentioning
confidence: 90%
“…We also point out that our simulation of the WT spike can, by fiat, only identify the residue to be mutated, but not the amino acid to which the residue will be mutated. However, both experimental and computer simulation studies have already established that D614G, A570D, and a few other mutations transform the dynamics of the RBD and favor an “up” state ( 54 , 55 , 59 , 61 , 72 ). In the current work, we highlighted a set of residues which show high correlation with RBD opening motion.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The first may disrupt a salt bridge with D30 of ACE2. The second may disrupt the interaction of RBD with K31 of hACE2 and enhance ACE2 binding 1,4 . Recent data have shown that VOC, especially those like B.1.351 with aa.…”
Section: Was Identified In Southmentioning
confidence: 99%
“…The D614G mutant prefers the one RBD "up" state ∼7 times more than the "3-down" configuration while they are equally likely in the wild type strain (52). The specific role of the D614G mutation was recently also established by coarse grained MD study (70) residues, but did not yet become as widespread as D614G, likely because it did not have substantial evolutionary advan-the RBD opening motion increases infectivity can only be resolved in vivo, given the complexity of the viral entry process. A number of experiments and computational studies indicated that binding to ACE2 is feasible only when the RBD is "up" (26)(27)(28)(29)(30).…”
Section: Concluding Discussionmentioning
confidence: 93%
“…While our study did not focus on actual mutants, the role of specific point mutations in the dynamics of RBD of the spike protein has been explored using MD simulation in the literature. (58,70) From the point of view of immediate therapeutic interventions, this study opens up the possibility of designing inhibitors that bind to the regions outside the RBD, thereby preventing infection by freezing RBD dynamics via steric restrictions on specific distant residues. Such treatments are less likely to be affected by the evolutionary adaptations in RBD sequence that the virus performs frequently to evade the immune response.…”
Section: Concluding Discussionmentioning
confidence: 99%